2002
DOI: 10.1073/pnas.052296399
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of nitric oxide synthase and modulation of the guanylate cyclase activity by corticotropin-releasing hormone but not urocortin II or urocortin III in cultured human pregnant myometrial cells

Abstract: The biological actions of corticotropin-releasing hormone (CRH) in the human myometrium during pregnancy and labor are unknown. We hypothesized that CRH may modulate the nitric oxide system, and influence myometrial relaxation͞contractility. Incubation of myometrial cells with CRH, but not urocortin II or urocortin III, for 8 -16 h significantly induced mRNA and protein expression of endothelial and brain but not inducible nitric oxide synthase (NOS) isoforms. This action resulted in increased activity of solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 57 publications
2
51
0
1
Order By: Relevance
“…[22][23][24][25][26][27][28] Higher NO values found in late preterm mothers compared with term mothers Table 2 complement those reports. [22][23][24][25][26][27][28] Some earlier studies reported a greater expression of the isoforms of NOS (eNOS, iNOS) in the myometrium of the preterm 'not in labour' group compared with all other groups: non-pregnant women, pregnant women in the early third trimester, and pregnant women at term (both before and after labour). 27,28 Since iNOS promotes inflammation, and inflammation in turn promotes pro-oxidant formation, this may explain why late preterm mothers and not term mothers had more elevated plasma NO concentrations and reduced erythrocyte antioxidant (GPx) activity Table 2. 12 High prooxidant levels, coupled with reduced antioxidants, signify a disturbance of the pro-oxidant-antioxidant balance otherwise known as oxidative stress.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…[22][23][24][25][26][27][28] Higher NO values found in late preterm mothers compared with term mothers Table 2 complement those reports. [22][23][24][25][26][27][28] Some earlier studies reported a greater expression of the isoforms of NOS (eNOS, iNOS) in the myometrium of the preterm 'not in labour' group compared with all other groups: non-pregnant women, pregnant women in the early third trimester, and pregnant women at term (both before and after labour). 27,28 Since iNOS promotes inflammation, and inflammation in turn promotes pro-oxidant formation, this may explain why late preterm mothers and not term mothers had more elevated plasma NO concentrations and reduced erythrocyte antioxidant (GPx) activity Table 2. 12 High prooxidant levels, coupled with reduced antioxidants, signify a disturbance of the pro-oxidant-antioxidant balance otherwise known as oxidative stress.…”
Section: Discussionsupporting
confidence: 62%
“…29,30 The placenta synthesises, on a weight-for-weight basis, more NO than the foetal membrane or the myometrium. 26 From early pregnancy, the mitochondria replete placenta influences maternal homeostasis and consumes about 1% of the basal metabolic rate of the pregnant woman. 31 The placenta in addition, is highly vascular and, on exposure to high maternal oxygen tension, generates superoxide ( Tables 1 and 2].…”
Section: Discussionmentioning
confidence: 99%
“…In mixed cultures, CRH receptor expression was barely detectable in stromal cells in vitro (data not shown). This might be due to tissue manipulation upon preparation of primary cell cultures, since studies on human myometrial cells have shown loss of CRH receptors as the number of passages of primary cultures increases (Linton et al 2001, Aggelidou et al 2002.…”
Section: Fishmentioning
confidence: 99%
“…9, No. 1,2003 reduced the number of escape failures and ACTH administration (100 mg/rat, i.p.) blocked this effect.…”
Section: Elevated Plus Maze (Epm)mentioning
confidence: 99%